A Case of Malaria Predisposing to Salmonella Bacteremia in a Returning Traveler from Nigeria - Robert Jakubowski; Lisa L. Steed; Susan E. Dorman; Camelia Marculescu (Case Reports in Infectious Diseases)
We describe a febrile adult returning to the U.S. from Nigeria. Malaria was diagnosed by rapid antigen testing, but recognition of invasive nontyphoidal Salmonella disease was delayed. While the moniker, “typhomalaria,” once used to describe an illness with features of malaria and typhoid fever, has fallen out of favor, it may nevertheless be a helpful reminder to clinicians that both infectious diseases can arise in the same patient. Blood cultures should be obtained routinely in febrile returning travelers from malaria-endemic regions, including those in whom the diagnosis of malaria has already been established.